Motor Vehicle Crash Severity Estimations by Physicians and Prehospital Personnel. (3rd July 2014) - Cleveland, Nathan; Colwell, Christopher; Douglass, Erica; Hopkins, Emily; Haukoos, Jason S.
Abstract Objective. To determine whether emergency physicians (EPs) and prehospital emergency medical services (EMS) personnel differ in their assessment of motor vehicle crash (MVC) severity and the potential for serious injury when viewing crash scene photographs. Methods. Attending and resident EPs, paramedics, and emergency medical technicians (EMTs) from a single emergency medicine system used a web-based survey platform to rate the severity of 100 crash photographs on a 10-point Likert scale (Crash Score) and the potential for serious injury on a 0–100% scale (Injury Score). Serious injury was defined as skull fracture or intracranial bleeding, spine fracture or spinal cord injury, intrathoracic or intraabdominal injury, or long bone fracture. Crash and Injury Scores were stratified into EP and paramedic/EMT (EMS) groups and the mean score was calculated for each photo. Spearman rank correlation coefficients with 95% confidence intervals (95% CI) and Bland-Altman plots were constructed to assess agreement. Secondary analyses were performed after categorizing data into quartiles based on participants' estimations of MVC severity. Results. A total of 54 attending and 53 resident EPs, 156 paramedics, and 34 EMTs were invited to participate in the survey. Of these, 39 (72%) attending and 46 (87%) resident EPs, 107 (69%) paramedics, and 17 (50%) EMTs completed the survey. A total of 183 (88%) surveys were completed in full. The overall Crash Score correlation coefficient between EPs and EMS was 0.98 (95% CI, 0.97–0.99). The Crash Score correlation coefficients for each quartile were 0.86 (0.57–0.97), 0.93 (0.85–0.96), 0.58 (0.16–0.85), and 0.88 (0.66–0.97), respectively. The overall Injury Score correlation coefficient between EPs and EMS was 0.98 (0.88–0.97). The Injury Score correlation coefficients for each quartile were 0.94 (0.48–0.91), 0.76 (0.50–0.92), 0.80 (0.69–1.00), and 0.94 (0.57–0.97), respectively. Conclusion. Although overall agreement between EPs and EMS personnel was excellent, differences in estimation of crash severity and potential for injury were identified among crashes estimated to be moderate in severity.